EVALUASI DAN OPTIMALISASI PERENCANAAN PAJAK DALAM RANGKA UNTUK MEMINIMALKAN PEMBAYARAN PAJAK PENGHASILAN BADAN (PPh) PADA PT “MKJ” DI SIDOARJO TAHUN 2015 - Miftha Kartika Juliansyah; Hari Hananto (Perpustakaan Universitas Surabaya, 2018)
The purpose of this study is to describe how the implementation of the right tax planning to tax savings, especially in this research are discussed regarding Income Tax (PPh) Agency. During this time there were already efforts made by PT “MKJ” to do tax planning but not optimal due to the limitations of his knowledge of tax planning. In the application of the tax planning should be analyzed first what kind of taxation issues facing the company in order for the implementation in the application of the tax planning goes well. This study is included within a qualitative study which is an applied research, which will provide solutions regarding the proper application of tax planning so that can help PT “MKJ” to minimize the taxes that must be paid. In this study uses data from the PT “MKJ”. In optimizing the implementation of tax planning, there is a strategy that can be done by PT